THE INFLUENCE OF ERGONOMIC ON WORKING FROM HOME ACTIVITIES - Imtihan Hanom; Rachel Aleyda Rozefy; Hilmiyani Taqiyyah Filasta (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Work From Home (WFH) is a system chosen by the government in 2020 due to the spread of the Corona virus, with this system it is hoped that it can maintain social distance, namely reducing people's mobility, maintaining physical distance, and reducing crowds so that it is expected to reduce the risk of corona virus transmission. and employee safety. The WFH system has high flexibility, this is to support employee balance between work and life. The work system that changed to WFH in a short period of time made workers experience stressful conditions such as feelings of anxiety or worry for a long time, especially when they lived under the same roof with many people. In carrying out WFH, workers need a comfortable place to work to help focus on work. One of the things that play a role in creating a sense of comfort when working is the application of ergonomic rules. This study looks for any variables that can affect WFH activities and which variables most affect WFH activities. The application of ergonomics, especially macro ergonomics in WFH activities, is considered appropriate to be able to solve various problems in WFH activities. This study uses a descriptive qualitative method by conducting a study through distributing questionnaires to respondents who are doing WFH. From the results of the study, it was found that the comfort of workers in carrying out WFH activities is closely related to ergonomics in a residential house. The results of this study can be used as a reference for designing a suitable workspace for WFH activities, and as a reference for further research with a similar focus of study. Keyword: Interior, Ergonomic, Working From Home